Design and Study of Walking Mechanism of Deformable Wheel-legged Robot - Jianhua Zhai; Fuxiao Wu; Xiaohua Wei; Haidong Luo (Jixie chuandong, 2021)
Aiming at the boundedness of wheel-legged type obstacle robot， a novel deformable wheel for wheel-legged obstacle crossing robot is designed to make the robot to switch between wheels and legs. The working principle of the wheel with variable structure is introduced. The mechanism executes wheeled mode on the flat road， and walks in wheel mode when encountering obstacles， it switches to a petals-type mode to cross obstacles. The process of straight-line moving， direction switching of the wheel in two modes is analyzed theoretically， and the kinematics simulation model is established. The kinematic simulation for the deploy progress is carried out in Adams to verify the theoretical analysis result. The simulation results show that the designed wheel structure possessed high capacity of obstacle climbing of the leg mechanism and stability of wheel mechanism， so the robot can adapt to a variety of complex road conditions.